2019
DOI: 10.1021/acs.jced.8b00930
|View full text |Cite
|
Sign up to set email alerts
|

Viscosities of Liquid Hexadecane at Temperatures between 323 K and 673 K and Pressures up to 4 MPa Measured Using a Dual-Capillary Viscometer

Abstract: We report viscosities of liquid hexadecane measured at temperatures between (323 and 673) K and at pressures up to 4.0 MPa. This study significantly extends the temperature range over which viscosity data for hexadecane are available. The experiments were carried out using a dual-capillary viscometer that measures the ratio of the viscosity at the temperature in question to that at a reference temperature, 298.15 K in this work, at which the viscosity is well known. Absolute viscosities were then obtained with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
(62 reference statements)
1
9
0
Order By: Relevance
“…(c) n -C 10 H 22 : ▲, this work; -----, reference correlation from Huber et al; △, Dymond and Young; ◮, Knapstad et al; ◭, Assael et al; triangle up top solid, Oliveira and Wakeham; triangle up bottom solid, Caudwell et al (d) n -C 16 H 34 : ●, this work; -----, reference correlation from Meng et al. ; ○, Nederbragt and Boelhouwer; ◑, Dymond and Young; ◐, Dymond et al; ◓, Wakefield and Marsh; ◒, Wakefield; circle lower right solid, Tanaka et al; circle upper left solid, Wu et al; circle lower left solid, Mohammed et al; circle upper right solid, Sanchez-Vicente et al . Dotted lines represent the uncertainties of the fits based on the average uncertainty of our experimental data.…”
Section: Results and Discussionmentioning
confidence: 84%
“…(c) n -C 10 H 22 : ▲, this work; -----, reference correlation from Huber et al; △, Dymond and Young; ◮, Knapstad et al; ◭, Assael et al; triangle up top solid, Oliveira and Wakeham; triangle up bottom solid, Caudwell et al (d) n -C 16 H 34 : ●, this work; -----, reference correlation from Meng et al. ; ○, Nederbragt and Boelhouwer; ◑, Dymond and Young; ◐, Dymond et al; ◓, Wakefield and Marsh; ◒, Wakefield; circle lower right solid, Tanaka et al; circle upper left solid, Wu et al; circle lower left solid, Mohammed et al; circle upper right solid, Sanchez-Vicente et al . Dotted lines represent the uncertainties of the fits based on the average uncertainty of our experimental data.…”
Section: Results and Discussionmentioning
confidence: 84%
“…The viscosity difference between the two fluids gives rise to a fingering instability at the interface known as the Saffman-Taylor instability 25 . Hexadecane viscosity reduces from 2.56 mPa.s to 1.28 mPa.s when the temperature is increased from 20 to 70 C 28 . As a result, it becomes easier for the aqueous phase to form the viscous finger at the oil–water interface and this phenomenon will also impact the drainage of the aqueous phase significantly.…”
Section: Discussionmentioning
confidence: 96%
“…From this can be concluded that it is the change in viscosity which impacts the thermal fluctuation time and hence, the rupture time of the thin film more than other parameters. When the temperature is increased from 20 to 70 C, the viscosity of water decreases from 1.0025 to 0.423 mPa s, which implies, almost by 60% 28 , 29 . On the other hand, the tensions at alkane-water interfaces are known to decrease slightly 30 , but nowhere as strongly as the viscosity.…”
Section: Discussionmentioning
confidence: 99%
“…The viscosity difference between the two fluids gives rise to a fingering instability at the interface known as the Saffman-Taylor instability 26 . Hexadecane viscosity reduces from 2.56 mPa.s to 1.28 mPa.s when the temperature is increased from 20 o C to 70 o C 23 . As a result, it becomes easier for the aqueous phase to form the viscous finger at the oil-water interface and this phenomenon will also impact the drainage of the aqueous phase significantly.…”
Section: Discussionmentioning
confidence: 95%
“…From this can be concluded that it is the change in viscosity which impacts the thermal fluctuation time and hence, the rupture time of the thin film more than other parameters. When the temperature is increased from 20 o C to 70 o C, the viscosity of water decreases from 1.0025 mPa.s to 0.423 mPa.s, which implies, almost by 60% 23,24 . On the other hand, the tensions at alkane-water interfaces are known to decrease slightly 25 , but nowhere as strongly as the viscosity.…”
Section: Discussionmentioning
confidence: 99%